Prioritising neonatal medicines research: UK Medicines for Children Research Network scoping survey - Hawcutt Daniel B; Lewis Sara; Turner Mark A; Field D (BMC, 2009)
Abstract Background The dosing regimen and indications for many medicines in current use in neonatology are not well defined. There is a need to prioritise research in this area, but currently there is little information about which drugs are used in UK neonatal units and the research needs in this area as perceived by UK neonatologists. Methods The Neonatal Clinical Studies Group (CSG) of the Medicines for Children Research Network (MCRN) undertook a 2 week prospective scoping survey study to establish which medicines are used in UK neonatal units; how many babies are receiving them; and what clinicians (and other health professionals) believe are important issues for future research. Results 49 out of 116 units responded to at least one element of the survey (42%). 37 units reported the number of neonates who received medicines over a 2 week period. A total of 3924 medicine-patient pairs were reported with 119 different medicines. 70% of medicine-patient pairs involved medicines that were missing either a license or dose for either term or preterm neonates. 4.3% of medicine-patient pairs involved medicines that were missing both license and dose for any neonate. The most common therapeutic gap in need of additional research identified by UK neonatologists was chronic lung disease (21 responding units), followed by patent ductus arteriosus and vitamin supplements (11 responding units for both) Conclusion The research agenda for neonatal medicines can be informed by knowledge of current medicine use and the collective views of the neonatal community.